(untitled) (Journal of Computational Mathematics, 1983)
Let A and B be m×n and p×n complex matrices respectively. This paper, as a continuation of the author's papers [7], discusses perturbation bounds for the generalized singular values of the Matrix-pairA,B in the case of rank( arrayc A B array )＜n.